Significados atribuidos a la comunicación, jerarquía y roles por un grupo de cuidadores primarios de personas con demencia. (2021)
Dementia is a degenerative disease that causes dependence on a primary caregiver and in turn the caregiver has difficulties, as Rojas et al (2020) expresses, the primary caregiver has psychological effects such as anxiety and depression and at the level of physical health such as fatigue, mental disorders. sleep and cardiovascular diseases; The objective of this work focused on describing the meanings attributed to communication, hierarchy and roles by a group of primary caregivers of people with dementia, with a method from the qualitative paradigm, a narrative design and establishing free (unstructured) interviews; resulting in distant communications between family members, roles and hierarchies that respond to the immediate care of the patient but do not account for a previous family organization, concluding that the patterns that family systems inherit to the next generations determine the stability and family climate in situations of high complexity, finally this work belongs to the line of research, Intervention and Changes in Systemic Contexts.